Awareness and Practices of Injury Prevention Strategies Among Ultimate Frisbee Players in Selangor, Malaysia - Cheng, Macullum Mak Geng; Vinosh Kumar, Purushothaman; Yughdtheswari, Muniandy; Sharmila Gopala Krishna, Pillai; Reshma, Praveen (Malaysian Physiotherapy Association, 2022)
Introduction: Among all club sports, Ultimate frisbee has one of the highest numbers of reported injuries. To reduce the overall burden of injury, developing and implementing effective, sport-specific injury prevention strategies should be a top priority. This study aimed to investigate the awareness on injury prevention strategies as well as commonly used injury prevention strategies among Ultimate frisbee players in Selangor, Malaysia. Methods: A cross-sectional study was conducted using an online self-administered questionnaire. Participants were recruited through various Ultimate frisbee clubs from social media via purposive sampling. Results: 211 eligible responses were obtained and over 72% of the players consider using proper technique in the game is important for preventing injuries. Over 50% of the participants were aware of factors such as proper technique (72.5%), stretching during warm-up (65.4%), warm-up (62.6%) and strength training as extremely important. Majority of participants practices injury prevention strategies such as stretching (82.9%), pre match general warm up (79.6%), fluid consumption following match (75.8%) and training session (73.9%). Conclusion: Hence, education for Ultimate frisbee players is recommended to promote the importance and benefits of different sports related injury prevention strategies to reduce the likelihood of injuries thus, enhancing sports performance.